Carbon dioxide injection: The importance of natural fractures in a tight reservoir for potential CO2 storage: A case study of the upper triassic - Middle Jurassic Kapp Toscana Group (Spitsbergen, Arctic Norway) - Ogata K.; Senger K.; Braathen A.; Tveranger J.; Olaussen S. (University of Tulsa, 2015)
A test was conducted in the Longyearbyen CO2 laboratory project to inject CO2 into a Triassic-Jurassic fractured sandstone-shale succession at 700-1000 m depth below the local settlement. Detailed investigation of fracture sets/discontinuities and their characteristics have been carried out, concentrating on the upper reservoir interval (670-706 m). The fracture distribution has a lithostratigraphical relationship and can be subdivided into massive to laminated shaly intervals, offering abundant lower-angle shear fractures, massive to thin-bedded, heterogeneous, mixed silty-shaly intervals, with a predominance of non-systematic, pervasive bed-confined fractures, and massive to laminated, medium- to thick-bedded, fine- to coarse-grained sandstones with a lower frequency of mostly steep fractures. The impact of these lithostructural domains on the fluid flow pathways in the heterolithic storage unit is discussed. Air poll control.